Designing a comprehensive Non-Communicable Diseases (NCD) programme for hypertension and diabetes at primary health care level: evidence and experience from urban Karnataka, South India - Krishnamurthy Jayanna; N. Swaroop; Arin Kar; Satyanarayana Ramanaik; Manoj Kumar Pati; Ashwini Pujar; Prathibha Rai; Suresh Chitrapu; Gururaj Patil; Preeti Aggarwal; Shivla Saksena; Hemanth Madegowda; et al. (BMC, 2019)
Abstract Background India accounts for more than two-third of mortality due to non-communicable diseases (NCDs) in south-east Asia. The burden is high in Karnataka, one of the largest states in southern India. There is a need for integration of disease prevention, health promotion, treatment and care within the national program at primary level. A public-private partnership initiative explored evidence gaps to inform a health system based, integrated NCD programme across care continuum with a focus on hypertension and diabetes. Methods The study was conducted during 2017-18 in urban parts of Mysore city, covering a population of 58,000. Mixed methods were used in the study; a population-based screening to estimate denominators for those with disease and at risk; cross-sectional surveys to understand distribution of risk factors, treatment adherence and out of pocket expenses; facility audits to assess readiness of public and private facilities; in-depth interviews and focus group discussions to understand practices, myths and perceptions in the community. Chi-square tests were used to test differences between the groups. Framework analysis approach was used for qualitative analysis. Results Twelve and 19% of the adult population had raised blood sugar and blood pressure, respectively, which increased with age, to 32 and 44% for over 50 years. 11% reported tobacco consumption; 5.5%, high alcohol consumption; 40%, inadequate physical activity and 81%, inappropriate diet consumption. These correlated strongly with elderly age and poor education. The public facilities lacked diagnostics and specialist services; care in the private sector was expensive. Qualitative data revealed fears and cultural myths that affected treatment adherence. The results informed intervention design across the NCD care continuum. Conclusions The study provides tools and methodology to gather evidence in designing comprehensive NCD programmes in low and middle income settings. The study also provides important insights into public-private partnership driving effective NCD care at primary care level.